Reliability and validity of the Addiction-Like eating behavior scale (AEBS) in a Peruvian adolescent population - Figueroa-Quiñones, Joel; Heredia, Nelly T. Condor; Cjuno, Julio; Yupanqui-Lorenzo, Daniel E.; Acharte-Champi, Walter Jesús; Fernandini-Valenzuela, Khristel (Frontiers in Psychology, 2025)
BackgroundUnderstanding eating behaviors in Latin American contexts is crucial, given the current epidemic of obesity among adolescents in this region.ObjectiveThe study aimed to analyze the psychometric properties of the Addiction-Like Eating Behavior Scale (AEBS) in adolescents from Peru.MethodologyThe study was psychometric in nature, conducted with a sample of 1,249 adolescents from coastal (Chimbote, n = 841) and jungle (Tarapoto, n = 408) cities in Peru. An exploratory factor analysis (EFA) was performed, and a scree plot was used to determine the factors. Additionally, a confirmatory factor analysis (CFA) was conducted to evaluate the goodness-of-fit indices used for structural validity, and the reliability of the Peruvian version of the AEBS was determined using McDonald's Omega.ResultsThe EFA reported the presence of three factors (KMO = 0.80 and p < 0.000). Furthermore, the CFA reported adequate fit indices (χ2 = 881.401; CFI = 0.957; TLI = 0.946; RMSEA = 0.074; and SRMR = 0.066) confirming the structure. The reliability was acceptable, with ω > 0.65 for all factors.ConclusionThe adapted version of the AEBS is valid and reliable for use with Peruvian adolescents.